STUDENTS’ PERCEPTION ON ORAL TESTS AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Sisca Novi Saputri (PBI 15 UMY 030, 2015)
*30 There are various kinds of tests in the learning process. The tests that were used by the lecturer could be in the form of written and oral. The research focused on the oral tests. An oral test has also been applied at English Education Department Universitas Muhammadiyah Yogyakarta (EED UMY). The present study aimed to describe the kinds of oral tests and students’ perception on oral tests at EED UMY. The researcher used qualitative research. The research was conducted at English Education Department Universitas Muhammadiyah Yogyakarta. The participants of this research consisted of six students of English Education Department batch 2012. In analyzing the data, the researcher used open, axial and selective coding. The findings of the research showed that kinds of oral tests that commonly used were in the forms of interviews, role plays, oral presentations, and group discussions. In addition, the findings related to the students’ perception on oral tests revealed the strengths and weaknesses of oral tests in class. The strengths of oral tests were that oral tests motivated the students to speak, enabled students get feedback, improved students’ speaking ability, developed students’ communication, improved students’ self-confidence, and gave ideas in speaking. Meanwhile, the students’ perception showed that the weaknesses of oral tests provided less time during test and made students nervous.